A Retrospective Evaluation of Response to Vitamin D Supplementation in Obese Versus Nonobese Patients. (December 2015) - Bryant, Ginelle A.; Koenigsfeld, Carrie Foust; Lehman, Nicholas P.; Smith, Hayden L.; Logemann, Craig D.; Phillips, Kirk T.
Objective: To evaluate the impact of body mass index (BMI) on vitamin D status following ergocalciferol therapy. Methods: A retrospective evaluation of patients aged 18 years and older with a baseline serum 25(OH)D < 30 ng/mL who received prescription ergocalciferol 50 000 IU at any dose between July 2009 and November 2011 was conducted. Patients were included if pre- and posttreatment 25(OH)D levels were available within 3 months of therapy. Results: Two hundred and thirteen patients were included in the study with 52% having a BMI ≥30 kg/m 2 . Thirty-eight different ergocalciferol regimens were prescribed, and the majority of patients (66.2%) received a regimen consisting of 50 000 IU once weekly for variable durations. Mean 25(OH)D levels increased from 18.8 ± 6.6 ng/mL at baseline to 35.0 ± 13.8 ng/mL with 61.0% (n = 130) of patients having attained vitamin D sufficiency, 25(OH)D ≥ 30 ng/mL, with their prescribed ergocalciferol regimen. Obese patients with a BMI ≥30 were less likely to attain vitamin D sufficiency following replacement than patients with a BMI <30 kg/m 2 (52% vs 71%; P = .0161). Conclusion: Our study demonstrated an overall moderate response rate to replacement therapy with ergocalciferol and considerable variability in vitamin D replacement strategies initiated by primary care providers. Based on our findings, elevated BMI ≥30 kg/m 2 may impact the likelihood of attaining vitamin D sufficiency with ergocalciferol.